2019
DOI: 10.1016/j.bjorl.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of intraoperative narrow-band imaging in transoral laser microsurgery for early and moderately advanced glottic cancer

Abstract: The intraoperative use of narrow-band imaging proved to be valuable in the visualization of suspect areas of the mucosa. Narrow-band imaging confirms the suspicions undertaken in white light and importantly, it showed microlesions beyond the scope of white light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…Among these, five primary research papers met the minimum eligibility criteria and were included in the systematic review. They included three retrospective studies , one descriptive study , and one prospective study . The main characteristics of the selected studies (type of study, length of follow‐up, and principal endpoint investigated) are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, five primary research papers met the minimum eligibility criteria and were included in the systematic review. They included three retrospective studies , one descriptive study , and one prospective study . The main characteristics of the selected studies (type of study, length of follow‐up, and principal endpoint investigated) are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Klimza et al reported the intraoperative use of NBI on a sample of 44 consecutive T1–T2 glottic cancers. All patients had clear margins in definitive histology and local recurrence was found in three of 44 patients (6.8%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,16 Thus, regarding the issue of white mucosal thickening, the surrounding mucosa should be analyzed for any vascular abnormalities with NBI. 5,15,19 Indeed, in the included studies 4,5,[14][15][16] reported that the SE and NPV of NBI were significantly greater than those of WL. In another study, Ni et al 16 reported that NBI was better than WL, especially concerning SP and PPV.…”
Section: Nbi Versus Wlmentioning
confidence: 94%
“…The aforementioned findings in NBI are identified as well-demarcated areas with scattered brownish spots [ 3 ]. It has been proven that narrow band imaging (NBI) is a useful tool in the detection of early glottic cancer and in the intraoperative delineation of superficial margins during cordectomy [ 4 6 ]. It has also been showed that NBI guides clinical decision-making regarding treatment of patients with laryngeal leukoplakia [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%